Can I control my bowel symptoms myself? The experience of controlling defaecation dysfunction among patients with rectal cancer after sphincter-saving surgery: a qualitative study - Wen Liu; Hai Ou Xia (International Journal of Qualitative Studies on Health & Well-Being, 2022)
Purpose To explore the experience of controlling defaecation dysfunction among patients with rectal cancer after sphincter-saving surgery. Methods This study applied a descriptive qualitative design. Thirty-six patients with rectal cancer were given semi-structured interviews in mainland China from February to July in 2019 after sphincter-saving surgery. Participants were recruited by purposive sampling. The thematic analysis approach was applied to analyse the transcripts. Results Three major themes emerged from the data were “having motivations of controlling defecation dysfunction”, “using strategies of controlling defecation dysfunction” and “facing barriers of controlling defecation dysfunction”. Conclusion Defaecation dysfunction makes obvious problems for patients after sphincter-saving surgery, although patients tried some self-care methods to cope with the defaecation dysfunction, some barriers still exist in the process of self-controlling of bowel symptoms. There is a strong demand for a systematic and scientific guideline for the self-management of defaecation dysfunction.